The Analysis of Diffusion and Priorities of ICT Centers in Rural Areas of Zabol - Gharib Fazelniya; Akbar Kiani; Ali Esmailzadeh (جغرافیا و پایداری محیط)
Information and Communication Technologies (ICTs) aid rural societies to encounter problems and difficulties intelligently and confront wisely with changes in economy, society and other fields. Some of the preconditions for the expansion of these technologies in rural areas are are enriching and improving the villagers living status, and, most importantly, considering the necessary substructures of ICTs. In the other hand, it is necessary to select the supreme village with suitable equipments for the substructures to present the better and useful services. For this purpose, the TOPSIS and Geographical Information System (GIS) methods are used in this thesis to select the supreme village in which each rural center is studied due to the following factors: the distance from Zabol, bank, postal, communication services, and information technologies. The six TOPSIS steps were done for each case and then the rural ICTs centers were prioritized. The outcomes of the research show that Lotfollah has an undesirable condition (0 ≤ 0.178 ≤ 1), but Teymor Abad has a pleasing condition (0 ≤ 0.991 ≤ 1). Local data gathered from the villages were saved in GIS, and then the required layer was established to prioritize the village and finally select the supreme rural center.